BUT DO NOT IDENTIFY AS GAY: A Proleptic Genealogy of the MSM Category - BOELLSTORFF, TOM (Cultural anthropology, 2011)
Growing numbers of persons worldwide are beginning to call themselves "men who have sex with men" or "MSM." How has this subject position come into being so swiftly, without the kind of social and political organizing associated with so many claims to identity? And how might considering this novel Jorm of selfhood help us craft anthropological responses to cultural phenomena whose conditions of historical emergence appear "untimely?" In this article, I develop a notion of "proleptic genealogy" to explore the origins of the MSM category, as well as transformations in the category with regard to enumeration, identity, and translocalization. In doing so, I show how anthropological inquiry can engage with emergent cultural logics through forms of anticipatory analysis.